Regioselective cobalt(II)-catalyzed [2 + 3] cycloaddition reaction of fluoroalkylated alkynes with 2-formylphenylboronic acids: easy access to 2-fluoroalkylated indenols - Kumon, Tatsuya; Shimada, Miroku; Wu, Jianyan; Yamada, Shigeyuki; Konno, Tsutomu (Beilstein Journal of Organic Chemistry, 2020)
[2 + 3] cycloaddition reactions of fluorinated alkynes with 2-formylphenylboronic acids under the influence of Co(acac)2·2H2O in two-component solvents of acetonitrile/2-propanol at reflux temperature for 18 h took place smoothly, affording the corresponding fluoroalkylated indenol derivatives in good yields. This reaction shows excellent regioselectivity, giving 2-fluoroalkylated indenols, together with a very small amount of 3-fluoroalkylated indanones as side products.
Keywords: [2 + 3] cycloaddition; cobalt catalyst; fluorine-containing; indenols; regioselective

(untitled) - Ishiguro, Y.; Okamoto, K.; Ojima, F.; Sonoda, Y. (Chem. Lett., 1993)

(untitled) - Clark, W. M.; Tickner-Eldridge, A. M.; Huang, G. K.; Pridgen, L. N.; Olsen, M. A.; Mills, R. J.; Lantos, I.; Baine, N. H. (J. Am. Chem. Soc., 1998)

(untitled) - Jiang, Z.-H.; Hwang, G.-S.; Xi, Z.; Goldberg, I. H. (J. Am. Chem. Soc., 2002)

(untitled) - Upadhayaya, R. S.; Shinde, P. D.; Kadam, S. A.; Bawane, A. N.; Sayyed, A. Y.; Kardile, R. A.; Gitay, P. N.; Lahore, S. V.; Dixit, S. S.; Földesi, A.; Chattopadhyaya, J. (Eur. J. Med. Chem., 2011)

(untitled) - Liebeskind, L. S.; Gasdaska, J. R.; McCallum, J. S.; Tremont, S. J. (J. Org. Chem., 1989)

(untitled) - Robinson, N. P.; Main, L.; Nicholson, B. K. (J. Organomet. Chem., 1989)

(untitled) - Quan, L. G.; Gevorgyan, V.; Yamamoto, Y. (J. Am. Chem. Soc., 1999)

(untitled) - Chang, K.-J.; Rayabarapu, D. K.; Cheng, C.-H. (J. Org. Chem., 2004)

(untitled) - Singh, P. P.; Reddy, P. B.; Sawant, S. D.; Koul, S.; Taneja, S. C.; Kumar, H. M. S. (Tetrahedron Lett., 2006)

(untitled) - Chinnagolla, R. K.; Jeganmohan, M. (Eur. J. Org. Chem., 2012)

(untitled) - Zhang, C.; Li, H.; Pei, C.; Qiu, L.; Hu, W.; Bao, X.; Xu, X. (ACS Catal., 2019)

(untitled) - Gu, C.-X.; Chen, W.-W.; Xu, M.-H. (J. Org. Chem., 2020)

(untitled) - Meanwell, N. A. (J. Med. Chem., 2018)

(untitled) - Zhou, Y.; Wang, J.; Gu, Z.; Wang, S.; Zhu, W.; Aceña, J. L.; Soloshonok, V. A.; Izawa, K.; Liu, H. (Chem. Rev., 2016)

(untitled) - Wang, J.; Sánchez-Roselló, M.; Aceña, J. L.; del Pozo, C.; Sorochinsky, A. E.; Fustero, S.; Soloshonok, V. A.; Liu, H. (Chem. Rev., 2014)

(untitled) - Kirk, K. L. (J. Fluorine Chem., 2006)

(untitled) - Bégué, J.-P.; Bonnet-Delpon, D. (J. Fluorine Chem., 2006)

(untitled) - Isanbor, C.; O’Hagan, D. (J. Fluorine Chem., 2006)

(untitled) - Allen, A. D.; Fujio, M.; Mohammed, N.; Tidwell, T. T.; Tsuji, Y. (J. Org. Chem., 1997)

(untitled) - Mitobe, K.; Terashima, K.; Kawasaki-Takasuka, T.; Agou, T.; Kubota, T.; Yamazaki, T. (Eur. J. Org. Chem., 2018)

(untitled) - Kumon, T.; Yoshida, K.; Yamada, S.; Agou, T.; Kubota, T.; Konno, T. (Tetrahedron, 2019)

(untitled) - Ghavtadze, N.; Fröhlich, R.; Bergander, K.; Würthwein, E.-U. (Synthesis, 2008)

(untitled) - Chinchilla, R.; Nájera, C. (Chem. Rev., 2014)

(untitled) - Gandeepan, P.; Cheng, C.-H. (Acc. Chem. Res., 2015)

(untitled) - Boyarskiy, V. P.; Ryabukhin, D. S.; Bokach, N. A.; Vasilyev, A. V. (Chem. Rev., 2016)

(untitled) - Jeon, S. L.; Kim, J. K.; Son, J. B.; Kim, B. T.; Jeong, I. H. (Tetrahedron Lett., 2006)

(untitled) - Kumon, T.; Yamada, S.; Agou, T.; Kubota, T.; Konno, T. (J. Fluorine Chem., 2018)

(untitled) - Ueda, M.; Ueno, T.; Suyama, Y.; Ryu, I. (Tetrahedron Lett., 2017)

(untitled) - Ernst-Russell, M. A.; Chai, C. L. L.; Wardlaw, J. H.; Elix, J. A. (J. Nat. Prod., 2000)

(untitled) - Morrell, A.; Placzek, M.; Parmley, S.; Grella, B.; Antony, S.; Pommier, Y.; Cushman, M. (J. Med. Chem., 2007)

(untitled) - Turek, M.; Szczęsna, D.; Koprowski, M.; Bałczewski, P. (Beilstein J. Org. Chem., 2017)

(untitled) - Cooke, E.; Paradellis, T. C.; Edward, J. T. (Can. J. Chem., 1982)

(untitled) - Barth, W.; Paquette, L. A. (J. Org. Chem., 1985)

(untitled) - Minatti, A.; Zheng, X.; Buchwald, S. L. (J. Org. Chem., 2007)

(untitled) - Lin, P.-S.; Jeganmohan, M.; Cheng, C.-H. (Chem. – Eur. J., 2008)

(untitled) - Hamada, Y.; Kawasaki-Takasuka, T.; Yamazaki, T. (Beilstein J. Org. Chem., 2017)